Lung ultrasound for assessing disease progression in UIP and NSIP: a comparative study with HRCT and PFT/DLCO - Nasrollahzadeh Milad; Idani Esmaeil; Abedini Atefeh; Malekshoaar Mehran; Sadeghi Mohsen; Kasravi Maryam; Tofighi Rozhin; Roostaei Ghazal; Kiani Arda (BMC Pulmonary Medicine)
Abstract Background This study aims to compare Lung Ultrasound (LUS) findings with High-Resolution Computerized Tomography (HRCT) and Pulmonary Function Tests (PFTs) to detect the severity of lung involvement in patients with Usual Interstitial Pneumonia (UIP) and Non-Specific Interstitial Pneumonia (NSIP). Methods A cross-sectional study was conducted on 35 UIP and 30 NSIP patients at a referral hospital. All patients underwent LUS, HRCT, and PFT. LUS findings such as B-lines, pleural fragmentation, and pleural thickening were compared with HRCT-based lung involvement and PFT parameters. Results In UIP patients, B-lines > 18 and pleural fragmentation significantly differentiated between < 50% and > 50% HRCT involvement. A logistic regression model showed that B-lines > 18 (OR = 39, p = 0.04) and pleural fragmentation (OR = 22, p = 0.037) independently predicted > 50% HRCT involvement. ROC analysis of the model revealed 84.2% sensitivity and 84.5% specificity. Furthermore, the crude number of B-lines (OR = 1.2, p = 0.038) and > 50% HRCT involvement (OR = 9.5, p = 0.045) independently predicted severe DLCO impairment, with a sensitivity of 94.7% and specificity of 84.5%. Linear regression showed that each additional B-line was associated with a 0.4% decrease in DLCO (Beta = -0.377, p = 0.043), independent of patient diagnosis. In NSIP patients, no significant correlation was observed between LUS findings and > 50% HRCT involvement (p > 0.05), though B-line numbers and pleural thickening increased in cases with severe DLCO impairment (p < 0.05). Conclusions LUS shows promise as a sensitive, radiation-free alternative to HRCT in monitoring the severity of UIP. It is particularly valuable in predicting the extent of lung involvement and severe DLCO impairment in UIP patients but has limited application in NSIP.